Characterization of Staphylococcus aureus Cas9: a smaller Cas9 for all-in-one adeno-associated virus delivery and paired nickase applications. Issue 1 (December 2015) - Friedland, Ari; Baral, Reshica; Singhal, Pankhuri; Loveluck, Katherine; Shen, Shen; Sanchez, Minerva; Marco, Eugenio; Gotta, Gregory; Maeder, Morgan; Kennedy, Edward; Kornepati, Anand; Sousa, Alexander; et al.
Abstract Background CRISPR-Cas systems have been broadly embraced as effective tools for genome engineering applications, with most studies to date utilizing theStreptococcus pyogenes Cas9. Here we characterize and manipulate the smaller, 1053 amino acid nucleaseStaphylococcus aureus Cas9. Results We find that theS. aureus Cas9 recognizes an NNGRRT protospacer adjacent motif (PAM) and cleaves target DNA at high efficiency with a variety of guide RNA (gRNA) spacer lengths. When directed against genomic targets with mutually permissive NGGRRT PAMs, theS. pyogenes Cas9 andS. aureus Cas9 yield indels at comparable rates. We additionally show D10A and N580A paired nickase activity withS. aureus Cas9, and we further package it with two gRNAs in a single functional adeno-associated virus (AAV) vector. Finally, we assess comparativeS. pyogenes andS. aureus Cas9 specificity using GUIDE-seq. Conclusion Our results reveal anS. aureus Cas9 that is effective for a variety of genome engineering purposes, including paired nickase approaches and all-in-one delivery of Cas9 and multiple gRNA expression cassettes with AAV vectors.